STRATEGI HUMAS PEMERINTAH DAERAH KABUPATEN MUNA BARAT DALAM MEMBERIKAN INFORMASI KEPADA MASYARAKAT - Anggraini, Luhani; Larisu, Zulfiah; Nurfkria, Ikrima (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2019)
ABSTRACT                              The purpose of this study was to determine the Public Relations Strategy of the West Muna Regency Government in Providing Information to the society. The subjects of this study were the entire staff / employees at the Regional Government Office of West Muna Regency with 6 informants. The technique for determining informants in this study is the purposive sampling technique. Data collection techniques used in this research are observation, interviews, literature study and documentation. While the data analysis technique used in this research is descriptive qualitative, which is describing, analyzing, describing the conclusions of the results of the research that are connected with relevant theories.                              The results showed that the Public Relations strategy of the Regional Government of West Muna Regency in providing information to the society through three (3) ways, namely through conventional media, public relations in collaboration with the print media of Kendari Pos, Buton Pos and Rakyat Sultra, and in collaboration with the media electronic TVRI Sultra, but in its use is more dominant using print media in providing information to the society, then through new media namely public relations in collaboration with online media or media news sites Zonasultra.com, Lenterasultra.com, and Sultrakini.com, but there are several media news sites that do not have a cooperative relationship with the West Muna Regency Government Public Relations but actively provide information about West Muna Regency, for example Penasultra.com, and the last strategy used by the West Muna Regency Government Public Relations is to provide information directly by inviting traditional figures in every activity carried out by the West Muna Regency Government Public Relations and direct socialization to the sosiety. Provision of this information is not only done by public relations but also delivered by the regents, deputy regents and the relevant regional work units (SKPD). Keywords: Public Relations Strategy; Regional Government; Information; Society